The Ambivalence of Platforms. Between Surveillance and Resistance in the Management of Vulnerable Populations - Olivieri, Lorenzo; Pelizza, Annalisa (Tecnoscienza – Italian Journal of Science & Technology Studies, 2021)
This contribution aims to summarize and highlight the main themes emerged during the panel “Surveillance infrastructures or open platforms? Aid and control of vulnerable populations through digital data” that took place at the VIII STS Italia Conference. The panel invited to reflect upon the ambivalence and ambiguity of digital platforms and data infrastructures for population management as well as on the highly diversified functions and users they support and attract. More precisely, presenters were encouraged to enquire how platforms and data infrastructures affect vulnerable populations and reconfigure the boundaries between the private and public domains: how do they allow empowering and innovative communication and resistance strategies? How, on the contrary, do they produce novel or exacerbate already existing vulnerabilities? How is the modern distinction between government, business, and civil society de facto reshuffled as a consequence? Although panel’s presentations discussed remarkably different types of platforms – from online maps and social networks to public health databases and migration technologies – they overall emphasized that only a careful, situated analysis of the multiple socio-technical factors shaping users’ engagement might help to understand how – and why – those technologies become tools for control and surveillance or empowerment resources.